Analysis and Design of Cavity-Backed Probe-Fed Hybrid Microstrip Antennas on FR4 Substrate - D. C. Nascimento; Prêntice C. Ribeiro Filho; Alexis F. Tinoco-S; J. C. da S. Lacava (International Journal of Antennas and Propagation)
A novel cavity-backed probe-fed linearly polarized microstrip antenna based on the concept of hybrid radiators is proposed and implemented. The resulting flush-mounted antenna exhibits symmetrical bandwidth, low cross-polarization radiation in the H-plane, due to its hybrid patch, and low cost, since it can be built on a FR4 laminate. Substrate integrated waveguide technology is used in the fabrication of the metallic cavity. The effect of mutual coupling is analyzed for two classical arrangements: the side-by-side and the collinear configurations.